The use of innovative technologies in the teaching of fine arts in the system of continuing education - Ergashev Madaminjon Yuldashevich (Research Parks Publishers, 2020)
In this article, the subject of fine arts, interest in the use of pedagogical and information technologies, interactive methods and innovative lessons in the educational process, non-traditional teaching methods, stratification, group work, conversation, discussion, database,